Prevalence and anatomical sites of human papillomavirus, Epstein-Barr virus and herpes simplex virus infections in men who have sex with men, Khon Kaen, Thailand - Chuerduangphui, Jureeporn (BMC Infect Dis, 2018)
BACKGROUND: Human papillomavirus (HPV), Epstein-Barr virus (EBV) and herpes simplex virus (HSV) cause sexually transmitted diseases (STDs) that are frequently found in men who have sex with men (MSM) with human immunodeficiency viral (HIV) infection. METHODS: This study investigated the prevalence of infection and anatomical site distribution of these viruses in asymptomatic MSM. DNA, extracted from cells collected from the anorectum, oropharynx and urethra of 346 participants, was investigated for the presence of EBV, HPV and HSV using real-time PCR. Demographic data from the participants were analyzed. RESULTS: All three viruses were found in all sampled sites. EBV was the commonest virus, being detected in the anorectum (47.7% of participants), oropharynx (50.6%) and urethra (45.6%). HPV and HSV were found in 43.9% and 2.9% of anorectum samples, 13.8% and 3.8% of oropharynx samples and 25.7% and 2% of urethra samples, respectively. HPV infection of the anorectum was significantly associated with age groups 21–30 (odds = 3.043, 95% CI = 1.643–5.638 and P = 0.001) and 46–60 years (odds = 2.679, 95% CI = 1.406–5.101 and P = 0.03). EBV infection of the urethra was significantly correlated with age group 21–30 years (odds = 1.790, 95% CI = 1.010–3.173 and P = 0.046). EBV/HPV co-infection of the anorectum (odds = 3.211, 95% CI = 1.271–8.110, P = 0.014) and urethra (odds = 2.816, 95% CI = 1.024–7.740, P = 0.045) was also associated with this age group. Among HIV-positive MSM, there was a significant association between age-group (odds = 21.000, 95% CI = 1.777–248.103, P = 0.016) in HPV infection of the anorectum. A failure to use condoms was significantly associated with HPV infection of the anorectum (odds = 4.095, 95% CI = 1.404–11.943, P = 0.010) and urethra (odds = 7.187, 95% CI = 1.385–37.306, P = 0.019). Similarly, lack of condom use was significantly associated with EBV infection of the urethra (odds = 7.368, 95% CI = 1.580–34.371, P = 0.011). CONCLUSION: These results indicate that asymptomatic MSM in Northeast Thailand form a potential reservoir for transmission of STDs, and in particular for these viruses. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12879-018-3406-0) contains supplementary material, which is available to authorized users.